Ocular expression of cyclin‐dependent kinase 5 in patients with proliferative diabetic retinopathy - Hiroki Sano; Kazuhiko Namekata; Masanori Niki; Kentaro Semba; Fumiko Murao; Takayuki Harada; Yoshinori Mitamura (Journal of Diabetes Investigation, 2022)
ABSTRACT Aims/Introduction Inhibition of peroxisome proliferator‐activated receptor gamma (PPARγ) phosphorylation mediated by cyclin‐dependent kinase 5 (Cdk5) is one of the main mechanisms of action of antidiabetic drugs. In this study, we analyzed the ocular expression and activation of Cdk5 in patients with proliferative diabetic retinopathy (PDR). Materials and Methods The concentrations of PPARγ, Cdk5 and its activating subunit (p35) were determined in the vitreous body of 24 PDR and 63 control eyes by enzyme‐linked immunosorbent assay. In addition, the messenger ribonucleic acid and protein expression levels of PPARγ, Cdk5 and p35 were measured in proliferative neovascular membranes from seven PDR eyes and non‐neovascular epiretinal membranes from five control eyes by quantitative real‐time polymerase chain reaction and immunohistochemical analysis. Results PPARγ, Cdk5 and p35 concentrations in the vitreous body were significantly higher in the PDR group compared with the control group. There was also a positive significant correlation of Cdk5 with PPARγ and p35 in the PDR group. Furthermore, the messenger ribonucleic acid expression levels of PPARγ, Cdk5 and p35 in proliferative neovascular membranes were significantly higher in the PDR group compared with the control group. Immunostaining showed increased protein expression levels of PPARγ, Cdk5 and p35 in proliferative neovascular membranes in the PDR group compared with the control group. Conclusions Cdk5 activation is involved in PDR pathogenesis through PPARγ expression, and inhibition of Cdk5‐mediated PPARγ phosphorylation might be a new therapeutic target for treatment of PDR.